2023
DOI: 10.1111/bph.16061
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal prostaglandin E synthase‐1 inhibition prevents adverse cardiac remodelling after myocardial infarction in mice

Abstract: Background and Purpose Heart failure with reduced ejection fraction (HFrEF) is a major consequence of myocardial infarction (MI). The microsomal prostaglandin E synthase‐1 (mPGES‐1)/PGE2 pathway has been shown to constrain reperfusion injury after acute myocardial ischaemia. However, it is unknown whether pharmacological inhibition of mPGES‐1, a target with lower risk of thrombosis compared with selective inhibition of cyclooxygenase‐2, affects chronic cardiac remodelling after MI. Experimental Approach Mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…In contrast, mPGES-1 deletion in myeloid cells improves the post-MI survival rate without affecting cardiac function, fibrosis, hypertrophy, and infarct size. 138 mPGES-1 inhibition, but not celecoxib, improves cardiac fibrosis and reduces infarct size after MI, 139 due to the shunting of PGH 2 to the cardioprotective PGI 2 . 139,140 The effect of PGE 2 in adult myocardium is mediated mainly by EPr2, EPr3, or EPr4.…”
Section: Pge 2 In Myocardial Remodelingmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, mPGES-1 deletion in myeloid cells improves the post-MI survival rate without affecting cardiac function, fibrosis, hypertrophy, and infarct size. 138 mPGES-1 inhibition, but not celecoxib, improves cardiac fibrosis and reduces infarct size after MI, 139 due to the shunting of PGH 2 to the cardioprotective PGI 2 . 139,140 The effect of PGE 2 in adult myocardium is mediated mainly by EPr2, EPr3, or EPr4.…”
Section: Pge 2 In Myocardial Remodelingmentioning
confidence: 98%
“…138 mPGES-1 inhibition, but not celecoxib, improves cardiac fibrosis and reduces infarct size after MI, 139 due to the shunting of PGH 2 to the cardioprotective PGI 2 . 139,140 The effect of PGE 2 in adult myocardium is mediated mainly by EPr2, EPr3, or EPr4. 3 EPr2 deletion exacerbates myocardial injury after MI by reducing inflammatory macrophages in the infarcted heart and thereby impairing cardiac repair.…”
Section: Pge 2 In Myocardial Remodelingmentioning
confidence: 98%
See 1 more Smart Citation
“…64,149 A recent study found that urine PGI2 content was positively correlated with cardiac ejection fraction after MI, and PGI2 played a protective role in cardiac remodeling independently of PGE2. 150 Notably, the IP knockout mice showed increased infarct size after heart reperfusion injury, while TAX2 receptor (TP) knockout had no effect. 64 In addition, myocardial-produced PGI2 acts directly on cardiomyocytes to exert MIR-protective effects independent of the effects on centrocytes and platelets, 64 which may explain that TP-KO does not affect MIR-progression.…”
Section: Biological Functions and Molecular Mechanisms Of Aa Pathway ...mentioning
confidence: 99%